Pelestarian Budaya Melayu dalam Filosofi Rumah Lontiok Melalui Eksplorasi Budaya di Desa Pulau Belimbing - Siti Nila Lestari; Suci Aulia Sya'ban; Nailaturrahmah Insani; Rahmi Fadillah; Putri Salisa; Elmustian Elmustian (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
The preservation of Malay culture, particularly through the philosophy of the Lontiok house, plays a significant role in maintaining the cultural identity and traditional values of the community. The Lontiok house, as a symbol of Malay culture, serves not only as a dwelling but also reflects the community's close relationship with nature and spirituality. This study aims to explore how the philosophy of the Lontiok house is preserved in Pulau Belimbing Village through the cultural practices in the local community. The research employs a qualitative approach, focusing on an in-depth understanding of the cultural phenomena that exist in the village. Data were gathered through direct observation, interviews with local residents, and relevant literature review. The findings show that the preservation of the Lontiok house in Pulau Belimbing Village is carried out not only through the construction and maintenance of the traditional house but also through cultural education, traditional ceremonies, and the development of culture-based tourism. The study also reveals that the community plays an active role in preserving and passing on the philosophy contained in the Lontiok house to the younger generation, ensuring the continuity of Malay cultural heritage. It is hoped that the results of this study can contribute to the future preservation of Malay culture and introduce the uniqueness of local culture to the outside world.